The prohibition of Israf in QS. Al-A'raf Verse 31 and Its Relevance to Environmental Conservation - Lestari, Ayu; Azizah, Alfiyatul (Universitas Muhammadiyah Surakarta, 2025)
Environmental degradation has become one of the most critical global challenges in contemporary society, primarily driven by excessive human consumption and the exploitative use of natural resources. Islam addresses this issue through ethical teachings that emphasize moderation and balance in human behavior. One of the key Qur'anic principles related to this issue is the prohibition of isrāf (extravagance), as stated in QS. Al-A'rāf verse 31: “Eat and drink, but do not be excessive. Indeed, Allah does not like those who are excessive.” This study aims to analyze the concept of isrāf in the Qur’an and to examine its relevance to environmental preservation using a thematic interpretation (tafsīr maudhū‘ī) approach. The research adopts a qualitative library-based method by collecting Qur’anic verses related to isrāf and analyzing them through classical and contemporary tafsir as well as Islamic environmental ethics perspectives. The findings indicate that isrāf in the Qur’anic worldview refers to any form of behavior that exceeds proper limits, including excessive consumption and irresponsible use of natural resources. QS. Al-A‘rāf verse 31 highlights moderation as a fundamental Islamic value and provides an ethical foundation for sustainable living. The prohibition of isrāf is therefore not merely a moral injunction but also a practical framework for addressing contemporary environmental crises. This study concludes that Islamic teachings on moderation and balance are highly relevant to modern sustainability efforts and can contribute significantly to the development of environmentally responsible behavior.